Investigation of OSN properties of PDMS membrane for the retention of dilute solutes with potential industrial applications. Issue 6 (7th August 2019) - Morshed, Mahbub; Simonaire, Hervé; Alem, Halima; Roizard, Denis
ABSTRACT: Few commercially available membranes can be used for organic solvent nanofiltration (OSN). Applying OSN in chemical industries is nevertheless of high interest to cut with energy consumption linked to solvent recycling and soluble catalysts recovery. A commercial membrane, PERVAP4060, was used to investigate the retention of dilute solutes in toluene feeds and to mimic metathesis medium. The studied solutes were R‐BINAP a neutral polyaromatic molecule used in metathesis chemistry, tetraoctylammonium bromide (ToABr), a charged molecule used as a homogeneous catalyst and n ‐hexadecane. Retention of polar ToABr (95%) was higher than that of neutral R‐BINAP (80%). The transfer mechanism, either pore flow or solution‐diffusion, was discussed. All the results obtained suggested that the transport is governed by the solution‐diffusion mechanism. The measured retentions could be explained in terms of solubility affinities and diffusion coefficients. The stability and performances of PERVAP4060 were well established, showing the strong potential for industrial applications. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2020, 137, 48359. Abstract : High rejection of diluted R‐BINAP from toluene together with high permeation of C16.